State of World Population 2022 - United Nations Population Fund (United Nations, 2022)
The State of World Population 2022 will take up the issue of unintended pregnancy and look at its drivers and impact. We will take a look at causes and consequences of unmet need for family planning, but also at the constellation of forces that can lead to an unintended pregnancy and at how that pregnancy can harm a woman’s or adolescent’s health, her earnings potential and more.